Expressive Speech Acts in Public Comments on Ferdy Sambo's Court Live Streaming on KompasTV Youtube - Apriliadhani, Norma Nirmana; Prayitno, Harun Joko (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study investigates expressive speech acts observed within the comments section of a YouTube channel. Specifically, the research aims to delineate the classification of expressive speech acts evident in public comments during Ferdy Sambo's court live streams on KOMPASTV's YouTube platform. Employing a descriptive qualitative approach, the study draws upon sentences or expressions representing expressive speech acts extracted from public comments during Ferdy Sambo's court proceedings on KOMPASTV's YouTube channel as its primary data and data source. Data collection was facilitated through note-taking techniques. Analysis of the collected data revealed several categories of expressive speech acts, including: (1) instances of anger, totaling six occurrences; (2) expressions of gratitude, amounting to five instances; (3) instances of satire, totaling four occurrences; (4) critical remarks, comprising a single instance; (5) expressions of astonishment, observed in four instances; and (6) manifestations of sadness, identified in two instances.